Automatic Bike as a Tool for Motor Development Programs for Children with Cerebral Palsy - Amani, Risca; Annisa, Annisa; Kurniawan, Yora; Unnazif, Dia (The Center for Disability Studies and Services Brawijaya University, 2021)
This article discusses the development and implementation of motor development tools to assist children with Cerebral Palsy. The failure to control motor function due to damage to the central nervous system has caused limbs stiffness resulting in the inability to carry out daily activities. The are some efforts to improve the limb stiffness for instance motor development activities to train muscles and joints. Utilizing a technology-based Automatic Bike can help implement the motor development program for children with Cerebral Palsy. The research includes a framework containing partners, problems, FGD, Automatic Bike, development, manuals and demonstration videos, FGD, information sharing, trials, results, and evaluation. Automatic Bike is a technology-based automatic bicycle that can be adjusted according to child's needs. This tool consists of pedals for upper and lower limbs which are driven by a motor. The implementation of the motor development program using Automatic Bike technology is carried out for four weeks frequently with a duration of 30 minutes a day. The continuous application of Automatic Bike can provide stimulus to both upper and lower limbs as the organs of movements, improving flex for joints and muscles stiffness along with increasing blood flow.